Pengaruh Harga, Promosi, Ulasan Produk, Dan Metode Pembayaran Terhadap Keputusan Pembelian Pada Marketplace TikTok Shop - Desita Pramudianti Eka Putri; Dewi Ayu Rismawati; Mukti Sri Lestari; Ninda Pravitasari; Peni Saputri; Roi Wahyudi; Yeni Rahmawati (Academica: Journal of Multidisciplinary Studies, 2023)
This research aimed to test the effect of prices; promotion; product reviews; and payment methods; on purchasing decisions on the TikTok Shop marketplace in Soloraya. This type of research is quantitative research. The sample used in this study was 100 respondents obtained using purposive sampling method. Data collection was taken by distributing questionnaires online via the Google form. Methods of data analysis, namely using the validity test; reliability test; classic assumption test; multiple linear regression analysis; t test; and F test. Data processing in this study uses the SPSS 23 application. The test results report that price (X1) has no effect on purchasing decisions; while Promotion (X2) has a significant positive effect on purchasing decisions; Product Reviews (X3) have a significant positive effect on purchasing decisions; and Payment Method (X4) has a positive and significant effect on Purchase Decisions at the TikTok Shop Marketplace in Soloraya. The implication of this research is that promotions, product reviews, and payment methods are factors that greatly influence consumer purchasing decisions on the TikTok Shop marketplace.